Public Religion and Secularization in England: Defending Bryan R. Wilson. (26th September 2016) - Bruce, Steve
Abstract: Matthew Wood's recent article in the European Journal of Sociology is a useful addition to the secularization debate. There is value in studying ways in which religious organizations now attempt to re-enter the public arena and the secularizing consequences of such activity. However, there is no justification for framing that case as an indictment of either Bryan R. Wilson's original 1966 presentation of the modern sociological secularization theory or the subsequent work of others in the same paradigm. This rejoinder explains Wilson's apparent assuming rather than demonstrating the declining influence of religious institutions and concludes that his work can be augmented without asserting that he had missed something which fundamentally alters the secularization approach to religious change.